2018
DOI: 10.1002/bjs.10978
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function after associating liver partition and portal vein ligation for staged hepatectomy in an experimental model

Abstract: Background Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is a two‐stage strategy to induce rapid regeneration of the remnant liver. The technique has been associated with high mortality and morbidity rates. This study aimed to evaluate mitochondrial function, biogenesis and morphology during ALPPS‐induced liver regeneration. Methods Male Wistar rats (n = 100) underwent portal vein ligation (PVL) or ALPPS. The animals were killed at 0 h (without operation), and 24, 48, 72 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 32 publications
(43 reference statements)
5
30
0
Order By: Relevance
“…Although preliminary studies have shown that mitochondrial function, hypoxia signals, and the pathways above are involved in ALPPS-induced regeneration, there is a lack of robust evidence to support the causality (7)(8)(9)(10)15). A deeper understanding of the activation of HSCs and the JNK1/IHH axis has been demonstrated as the first example of an ALPPS-induced molecular event associated with unprecedented regenerative acceleration (7,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although preliminary studies have shown that mitochondrial function, hypoxia signals, and the pathways above are involved in ALPPS-induced regeneration, there is a lack of robust evidence to support the causality (7)(8)(9)(10)15). A deeper understanding of the activation of HSCs and the JNK1/IHH axis has been demonstrated as the first example of an ALPPS-induced molecular event associated with unprecedented regenerative acceleration (7,16).…”
Section: Discussionmentioning
confidence: 99%
“…The Indian Hedgehog (IHH) pathway, mitochondrial function, and the transcriptional landscape during ALPPSinduced regeneration have been previously illustrated (7)(8)(9)(10). However, attenuation of regeneration in livers with fibrosis during ALPPS has not been well documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional evaluations of mitochondrial activity in rodents have demonstrated that, like human beings, I/R clearly affects mitochondrial function, which has implications for bioenergetics, and translates into lower energy production efficiency 32, 33. This ATP deficiency is sufficient to trigger changes in cellular metabolism; therefore, I/R injury in liver transplants interferes with the cellular bioenergetic balance.…”
Section: Discussionmentioning
confidence: 99%
“…In a very interesting study in a rodent model, Budai et al . found that, compared with portal vein ligation, associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is associated with pronounced bioenergetic derangement and decreased expression of peroxisome proliferator‐activated receptor γ co‐activator 1‐α (PGC1‐α), a key regulator mitochondrial biogenesis.…”
mentioning
confidence: 99%